Social aspects of the professionalization of midwives in Luxembourg (1800–1940) - Manon Pinatel (Theatrum Historiae)
This article proposes an open, interdisciplinary approach to understanding how women assisting at birth in Luxembourg in the late eighteenth century evolved to become specialised medical professionals in the early twentieth century. To do this, it is necessary to study the administrative organisation of training, recruitment policies and the form and content of the courses involved in the creation of a new health worker: the midwife. This individual often assumed the role of midwife, vaccinator, doctor of the poor or paediatric nurse.